2000
DOI: 10.1097/00004647-200003000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Acute Decrease in Cerebral Nitric Oxide Levels after Subarachnoid Hemorrhage

Abstract: Summary: Disturbances in the nitric oxide (NO) vasodilatory pathway have been implicated in acute vasoconstriction and ischemia after subarachnoid hemorrhage (SAH). The authors hypothesize that blood released during SAH leads to vasocon striction by scavenging NO and limiting its availability. This was tested by measuring the major NO metabolites nitrite and nitrate in five different brain regions before and after experi mental SAH. The basal NO metabolites levels were as follows (mean ± SO, f.Lmol/mg wet weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 44 publications
5
99
0
6
Order By: Relevance
“…In the brain, this tonic level of NO includes the release of NO due to neuronal activity, some of which also affects the vascular tone. SAH was recently shown to affect the short-term levels of NO in the rat brain as measured by assaying the metabolites nitrite and nitrate (121). Between 10 and 120 or 180 min after SAH, there were significantly decreased levels of these metabolites in the 5 regions studied, although recovery towards baseline levels had commenced by 180 min.…”
Section: Nos Expression /Activity After Sahmentioning
confidence: 99%
“…In the brain, this tonic level of NO includes the release of NO due to neuronal activity, some of which also affects the vascular tone. SAH was recently shown to affect the short-term levels of NO in the rat brain as measured by assaying the metabolites nitrite and nitrate (121). Between 10 and 120 or 180 min after SAH, there were significantly decreased levels of these metabolites in the 5 regions studied, although recovery towards baseline levels had commenced by 180 min.…”
Section: Nos Expression /Activity After Sahmentioning
confidence: 99%
“…This time course of HCN1 channel changing is earlier than that of cerebral vasospasm occurring, and closely followed by the time when cortical spreading depolarization begin to appear (Dreier et al, 2006). Additionally, it is generally accepted that the scavenging effect of Hb on NO signaling contributes to a series of pathological changes after SAH (Sehba et al, 2000;Koźniewska et al, 2006;Pluta et al, 2009) and the level of NO determines the neural susceptibility for cortical spreading depolarization after SAH (Petzold et al, 2008). In the current study, the scavenging effect of Hb on NO was observed.…”
Section: Discussionmentioning
confidence: 96%
“…Following this vasoconstriction, a delayed vasospasm appears, usually more than 48 h after that, as pioneering studies in rats revealed [29,30]. Many theories have tried to explain how this delayed vasospasm occurs, among them an alteration in the production of nitric oxide (NO) by the vascular endothelium [31], hence impairing the vasodilatory activity of this gas and the hemodynamic cerebral autoregulation. Following haemorrhage haemoglobin binds to NO, therefore decreasing its availability [32].…”
Section: Discussionmentioning
confidence: 99%